Corporate Governance in Banking and Investor Protection From Theory to Practice (CSR, Sustainability, Ethics & Governance,, 2018)
This book explores the status quo of corporate governance in banking and investor protection from both theoretical and practical perspectives. Bringing together original conclusions with a regional and international focus, it provides a timely and comprehensive overview of the effectiveness of corporate governance in the financial sector and an assessment of investor protection. It also includes a number of examples and case studies to illustrate the findings. The book compares corporate governance in the banking and financial industries before and after the financial crisis, and helps to evaluate the effect of the recommendations and regulations that have been developed in the interim.